PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN METODE JARIMATIKA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 188 PEKANBARU - Meriaty Tampubolon Meriaty Tampubolon; Lazim Lazim; Neni Hermita Neni Hermita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of this research is the low learning outcomes of Mathematics class IIB students in the know 15 out of 38 students who achieved KKM with an average score of 64.08. The purpose of this study was to improve the learning outcomes of mathematics by applying cooperative learning models using the Jarimatika method for students of class IIB SD Negeri 188 Pekanbaru. This study uses a Classroom Action Research (CAR) design which is carried out in two cycles and each cycle consists of four stages, namely planning, implementing, observing and reflecting. Data collection techniques used in this research are test techniques and observation techniques. All data were analyzed descriptively statistics. The subjects of this study were students of class IIB SDN 188 Pekanbaru which numbered 38 students. The results showed that classical completeness in cycle I was 68.42% which had an increase in cycle II of 84.21%. The average teacher activity in the first cycle was 66.67% increasing in the second cycle to 87.50%. Likewise, student activity in the first cycle was 62.50% increasing in the second cycle to 87.50%. The average score of the base score to cycle I increased from 64.08 to 73.45. From cycle I to cycle II it increased to 84.71. Based on the results of the research that has been carried out it can be concluded that the application of cooperative learning models using the Jarimatika method can improve the learning outcomes of student class II SDN 188 Pekanbaru